2022
DOI: 10.1002/bse.3206
|View full text |Cite
|
Sign up to set email alerts
|

Research and development intensity, environmental performance, and firm value: Unraveling the nexus in the energy sector worldwide

Abstract: The lack of a focused study on the nexus of research and development (R&D) intensity, eco-friendly practices, firm value in the energy sector, and the stakeholders' concerns for ecology motivated us to realize this study. The study sample covers the period from 2002 to 2019, resulting in 4016 firm-year observations affiliated with 43 countries. The data were retrieved from the Thomson Reuters Eikon, and a country-year fixed-effects regression analysis was executed. Our empirical findings are threefold. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 101 publications
2
18
0
Order By: Relevance
“…This includes spending and investing in systems and equipment to treat GHG emissions, waste, soil and water pollution, but also investing in environmental prevention and environmental R&D and innovation (Seles et al, 2018), since, according to study results, both strategies lead to improve stock returns. Indeed, investment in R&D encourages the emergence of environmental practices through which the organisation's environmental commitment is demonstrated to shareholders (Uyar et al, 2022). The results obtained are in line with previous research that positively relates investments in environmental protection and environmental R&D to market performance and business valuation (Grassmann, 2021; Hoang et al, 2020; Puertas et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes spending and investing in systems and equipment to treat GHG emissions, waste, soil and water pollution, but also investing in environmental prevention and environmental R&D and innovation (Seles et al, 2018), since, according to study results, both strategies lead to improve stock returns. Indeed, investment in R&D encourages the emergence of environmental practices through which the organisation's environmental commitment is demonstrated to shareholders (Uyar et al, 2022). The results obtained are in line with previous research that positively relates investments in environmental protection and environmental R&D to market performance and business valuation (Grassmann, 2021; Hoang et al, 2020; Puertas et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hoang et al (2020) companies' involvement in sustainable innovation along with an increasing environmental disclosure positively influence market performance. In sectors such as energy, R&D stimulates environmental practices related to the reduction of emissions, the reduction of resources consumption and eco‐innovation, which are favourably perceived by shareholders (Uyar et al, 2022). Specifically, the disclosure of environmental capital expenditure in the electricity utility sector is strongly correlated with lower emission rates and superior financial performance (Silva‐Gao, 2012).…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
“…Existing literature has already confirmed the positive effects of green initiatives on firms' financial performance (L opez-Pérez et al, 2017) and value (Ammer et al, 2020;Uyar et al, 2023). Another string of studies has demonstrated the positive impact of the TBL approach on firm value (Guenster et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…Following previous studies (e.g., Pindado et al 2008;Tinoco and Wilson 2013;Shahwan 2015;Chung et al 2015;Chen et al 2020;Uyar et al 2022;Mangena et al 2020), we used the logistic regression to examine the effect of firm-level and country-level governance structures on financial distress in a developing context, namely the MENA region. A Binary logistic model allowed us to generate the financial distress likelihood (FDL) for each bank to examine the accuracy of this prediction (Mangena et al 2020;Chung et al 2015).…”
Section: Model Specificationmentioning
confidence: 99%